Исследование материалов и элементов конструкций пневматическими измерителями - Малашенко С. В. Сергей Васильевич; Чекин О. Н. Олег Никонович; Дышель М. Ш. Маркс Шулимович; Милованова О. Б. Ольга Борисовна; Дадамухамедов Э. У. Элеонард Убайдуллаевич (Киев, Наукова думка, 1983)
Авт. указаны на обороте тит. л.